Impacto da presença de outliers na estimativa de teores, volumes e tonelagens: estudo de caso em uma mina de ferro no quadrilátero ferrífero, Minas Gerais - (:unkn) unknown (Universidade Federal do Pampa, 2026)
This study investigates the impact of outliers on grade estimation of grades, volumes and tonnages of iron ore in a mine located in the Quadrilátero Ferrífero, Minas Gerais, Brazil. Iron ore plays a strategic role in the global economy, which reinforces the need for reliable estimates to support the planning and viability of mining projects. Extreme values can distort statistical and geostatistical analyses, significantly affecting the mean, variance, and spatial continuity of grades. The study aims to perform a comparative analysis between estimates made with and without outlier treatment, using ordinary kriging (OK) as the primary tool, assessing the impact on average grades and resource volumes/masses. Descriptive statistical techniques, detection tests, and approaches such as outlier removal, geological grouping, and variable transformation are applied. The analysis considers both statistical and geological criteria to distinguish measurement errors from valid subpopulations. The results demonstrate how the chosen approach influences the mean, variance, and spatial continuity, indicating that outliers directly affect grade distribution and highlighting the importance of appropriate treatment to ensure the reliability of estimates. The study also proposes recommendations for outlier handling in geologically complex settings, aligned with the guidelines of international codes for resource and reserve estimation and classification, in order to improve the reliability of mineral estimates.
Keywords: Modelagem geoestatística; Variabilidade de teores; Krigagem ordinária; Estimativa mineral; Minério de ferro; Quadrilátero Ferrífero; Geostatistical modeling; Grade variability; Ordinary kriging; Mineral estimation; Iron ore; CIENCIAS EXATAS E DA TERRA